Monitoring Activities On Student Abilities And Obstacles During English Learning Process - Krisna Dwi Alifhia Rezky; Sabarun, Sabarun; Qamariah, Zaitun (PT. Padang Tekno Corp, 2024)
This article was written to help readers understand the results of reading activities and the abilities and obstacles experienced by students during the learning process. understand the results of monitoring achievement activities and abilities and obstacles experienced by students during the learning process. Monitoring is the routine data collection and process of targeting program targets that emphasizes the process and core of change. program target-targeting process that emphasizes process and kernel changes. the quality of the services we purchase while also keeping an eye on our accounts of what is done.